Dampak Penggunaan Gadget terhadap Perkembangan Siswa di SDN Banjaranyar 05 Brebes - Muhammad Fiqri Abdul Thoriq; Taukhid Mubarok (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This article aims to understand the impact of gadget use on childhood as well as implement solutions on the impact of gadget use on childhood. This gadget is a medium used as a modern communication tool. Gadgets make human communication easier. Today, communication has become more advanced with the advent of gadgets. Among them, 4,444 are smartphones such as iPhones, Androids and laptops. In preschool psychology, development refers to children from 0 to 6 years old. The research method used is literary research. Results show that amenities impact social development in young children. Excessive use of gadgets harms children's social and emotional development. Harmful effects of electronic device use on children include isolation, sleep disturbances, loneliness, violent behavior, reduced creativity and threats of cyberbullying. Solution to device use in childhood by limiting device use, supervising children's screen time with parents who play a crucial role, and providing a schedule timely when children play with devices, so that devices do not hinder young children's social development.